The effects of work stress and trust in managers on employee turnover intentions - Sebastian Urieși (CES Working Papers, 2019)
Employee turnover is detrimental for the general performance of any company, thus the factors that enhance employees' intentions to leave their company should be identified and addressed. The present study examined the impact of work stress and employees' trust in managers in this respect. Work stress was conceptualized through three inter-related dimensions, workload, low rewards and overcommitment, which we expected to affect also employees' trust in their managers. The study was performed on a sample of Romanian employees from several work-sectors. Results show that all three dimensions of work stress are positively related to turnover intentions, and that employees' perceptions of low rewards and their overcommitment negatively affect their trust in managers. Moreover, the latter emerged as a protective-factor against turnover intentions. Overall, this pattern of findings indicates a significant influence of work stress on turnover intentions, which's partially mediated by its undermining effect on employees' trust in their managers.
Keywords: 330; turnover intentions; work-stress; trust in managers